A catalyst for reforming methane into synthesis gas and a method for preparing the same

CN122999211APending Publication Date: 2026-10-30ANHUI NORMAL UNIV
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611525484.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-09-29
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0004]本发明的目的在于提供一种甲烷重整制合成气催化剂及其制备方法,以解决背景技术中提出的现有催化体系普遍存在催化活性不足、高温结构稳定性弱、抗积碳与抗烧结性能差、合成气配比调控精度低,以及成本较高等问题

Benefits of technology

[0017]本发明提供了一种外溶型钙钛矿催化剂及其制备方法并应用于甲烷重整制合成气。本发明的催化剂通过在钙钛矿A位同时引入双助剂,利用两者离子半径与价态的差异产生协同效应,一方面调节氧空位浓度,优化电荷传输与晶格氧活性;另一方面调变碱性位点的数量与强度,增强反应底物的吸附与活化能力,有效抑制了金属烧结与积碳,同时促进了镍纳米颗粒在钙钛矿表面溶出,增加了活性组分镍在钙钛矿表面的分散度,增加了催化剂的比表面积和活性组分与载体的相互作用,使其在高温甲烷重整制合成气中表现出优异的催化活性与长周期稳定性,通过调节进料组成,可获得H2/CO摩尔比在1.0~3.0范围内可调控的合成气,灵活匹配下游甲醇合成、费托合成、羰基合成等不同工艺对原料气组成的差异化需求。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122999211A_ABST
    Figure CN122999211A_ABST
Patent Text Reader

Abstract

The application belongs to the technical field of catalysts, and discloses a catalyst for methane reforming to prepare synthesis gas and a preparation method thereof.The preparation method comprises the following steps: S1, weighing a nickel source, a lanthanum source, a titanium source and M metal salt, stirring and dissolving in ethanol, and then stirring and dissolving citric acid and ethylene glycol to obtain a hydrogel; S2, drying into a perovskite oxide La a1 M a2 Ti b1 Ni b2 O x precursor, wherein the total molar sum of La and M is a1+a2 and 0.5≤a1+a2<1, the total molar sum of Ti and Ni is b1+b2 and is 1, heating at 350-450 ℃, and grinding and calcining after cooling; and S3, reducing under a hydrogen atmosphere to obtain the catalyst.The application effectively inhibits metal sintering and carbon deposition, exhibits excellent catalytic activity and long-period stability in high-temperature methane reforming to prepare synthesis gas, and can obtain synthesis gas with a H2 / CO molar ratio in the range of 1.0-3.0 by adjusting the feed composition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalyst technology, specifically relating to a catalyst for methane reforming to syngas and its preparation method. Background Technology

[0002] Methane and carbon dioxide are the two most concentrated greenhouse gases in the atmosphere, and their excessive emissions have become a major cause of global climate change and ecological imbalance. Achieving efficient resource conversion and utilization of these greenhouse gases is an important research direction for the green and low-carbon transformation of the chemical industry. Dry methane reforming (DRM: CH4 + CO2 = 2CO + 2H2) and steam methane reforming (SRM: CH4 + H2O = CO + 3H2) are two promising greenhouse gas resource utilization technologies. By adjusting the feed ratio of methane, carbon dioxide, and steam (dual methane reforming: 3CH4 + CO2 + 2H2O = 4CO + 8H2), syngas (H2 and CO) with an adjustable H2 / CO molar ratio within the range of 1.0 to 3.0 can be obtained. This controllability allows for adaptation to the varying requirements of downstream chemical synthesis processes regarding syngas composition: when the H2 / CO molar ratio is approximately 1.0, the syngas is suitable for carbonyl synthesis and the production of products such as acetic acid; when the H2 / CO molar ratio is approximately 2.0, it can be directly used for methanol synthesis and Fischer-Tropsch synthesis to produce liquid fuels; and when the H2 / CO molar ratio is between 2.5 and 3.0, it is suitable for processes requiring a high hydrogen-rich atmosphere, such as hydroformylation and hydrocracking. Therefore, by flexibly controlling the product composition, the application scope of syngas in downstream multi-product co-production systems can be effectively broadened, demonstrating promising prospects for industrial application.

[0003] However, existing reforming catalysts generally struggle to adapt to both dry reforming and dual reforming reaction systems simultaneously, making it difficult to precisely control the syngas ratio based on the differences in reaction system components, resulting in poor stability of the product gas ratio. Furthermore, existing catalytic systems generally suffer from insufficient catalytic activity, weak high-temperature structural stability, poor resistance to coking and sintering, low precision in syngas ratio control, and high cost, severely hindering the industrial-scale promotion of greenhouse gas reforming to syngas technology. Therefore, developing a novel reforming catalyst that combines low cost, high activity, excellent high-temperature stability, strong resistance to coking and sintering, and the ability to adapt to both types of reforming reaction systems while achieving precise control of the syngas ratio over a wide range has become a crucial technological direction urgently needing breakthroughs in this field. Summary of the Invention

[0004] The purpose of this invention is to provide a catalyst for methane reforming to syngas and its preparation method, so as to solve the problems of insufficient catalytic activity, weak high-temperature structural stability, poor anti-coking and anti-sintering performance, low precision of syngas ratio control, and high cost of existing catalytic systems mentioned in the background art.

[0005] To achieve the above objectives, the present invention provides a method for preparing a catalyst for methane reforming to syngas, comprising the following steps:

[0006] S1. Weigh out the nickel source, lanthanum source, and titanium source that constitute the perovskite body, then weigh out the M metal salt, add ethanol and stir to dissolve, then add citric acid and ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel.

[0007] S2. Dry the hydrogel until it becomes a dry gel precursor, namely, a perovskite oxide La with A-site defects and modified by the introduction of two additives. a1 M a2 Ti b1 Ni b2 O x The precursor, wherein the A-site elements include La and M, the total molar sum of La and M is a1+a2, and 0.5≤a1+a2<1, M is at least two of Ba, Sr, Mg, Ca, Ce, and Zr, and the B-site elements include Ti and Ni, the total molar sum of Ti and Ni is b1+b2, is 1. The dry gel precursor is heat-treated at a temperature of 350~450℃ for 0.5~2 hours, cooled to room temperature and then thoroughly ground. The ground sample is then transferred to a muffle furnace for calcination.

[0008] S3. The calcined sample was reduced to the catalyst La under a certain temperature and hydrogen atmosphere. a1 M a2 Ti b1 Ni b2 O x .

[0009] In one specific embodiment, the catalyst La a1 M a2 Ti b1 Ni b2 O x The Ni metal content is 9-21 wt% and the M metal content is 4-30 wt% by total catalyst weight. The preferred catalyst is La. a1 M a2 Ti b1 Ni b2 O x The total weight of the catalyst is 11-15 wt% Ni and 5-25 wt% M.

[0010] In one specific implementation, the total molar sum of the A-position elements, a1+a2, is 0.6~0.9; the total molar sum of the B-position elements, b1+b2, is 1, where b2 is 0.2~0.7. The total molar sum of the B-position elements, b1+b2, is 1, where b2 is 0.3~0.6.

[0011] In one specific embodiment, the nickel source is one of nickel nitrate hexahydrate, nickel acetylacetonate, and nickel chloride; the lanthanum source is one of lanthanum nitrate hexahydrate, lanthanum acetylacetonate, and lanthanum chloride; the titanium source is one of tetrabutyl titanate, titanium nitrate, and titanium acetylacetonate; and the M metal salt is one of barium nitrate, strontium nitrate, magnesium nitrate hexahydrate, calcium nitrate tetrahydrate, cerium nitrate hexahydrate, zirconium nitrate pentahydrate, barium acetylacetonate, strontium acetylacetonate, magnesium acetylacetonate, calcium acetylacetonate, cerium acetylacetonate, zirconium acetylacetonate, barium chloride, strontium chloride, magnesium chloride, calcium chloride, cerium chloride, and zirconium chloride.

[0012] In one specific embodiment, in step S1, the molar ratio of citric acid to all metal ions is 1~4:1; the molar ratio of ethylene glycol to all metal ions is 0.5~2:1; all metal ions include A-site element metal ions and B-site element metal ions; in step S2, the calcination temperature is 700~900℃ and the calcination time is 0.5~10 hours; in step S3, the reduction temperature is 700~900℃ and the reduction time is 0.5~10 hours.

[0013] In one specific embodiment, in step S1, the molar ratio of citric acid to all metal ions is 1~2.5:1; the molar ratio of ethylene glycol to all metal ions is 0.6~1.5:1; in step S2, the calcination temperature is 750~850℃ and the calcination time is 2~8 hours; in step S3, the reduction temperature is 750~850℃ and the reduction time is 1~4 hours.

[0014] The present invention also provides a catalyst for the reforming of methane to syngas, wherein the catalyst for the reforming of methane to syngas is prepared by the method for preparing the catalyst for the reforming of methane to syngas as described above.

[0015] The present invention also provides a method for producing syngas from methane reforming, which uses the catalyst for producing syngas from methane reforming as described above. The catalyst for producing syngas from methane reforming is placed in a fixed-bed reactor. The reaction conditions for producing syngas from methane reforming include: the reaction for producing syngas from methane reforming is carried out in a fixed-bed reactor, the reaction temperature is 600~900℃, the reaction pressure is 0~4MPa, the reaction space velocity is 5000~60000mL / g / h, and the molar ratio of methane, carbon dioxide and water vapor is 0.5~5:0.5~5:0~10.

[0016] Compared with the prior art, the present invention has the following beneficial effects:

[0017] This invention provides an externally dissolved perovskite catalyst and its preparation method, applied to the production of syngas from methane reforming. The catalyst of this invention introduces two promoters simultaneously at the A-site of the perovskite, utilizing the difference in their ionic radii and valence states to generate a synergistic effect. On the one hand, it adjusts the oxygen vacancy concentration, optimizing charge transport and lattice oxygen activity; on the other hand, it modulates the number and intensity of basic sites, enhancing the adsorption and activation capacity of the reaction substrate, effectively inhibiting metal sintering and carbon deposition, while simultaneously promoting the dissolution of nickel nanoparticles on the perovskite surface, increasing the dispersion of the active component nickel on the perovskite surface, increasing the specific surface area of ​​the catalyst, and enhancing the interaction between the active component and the support. This results in excellent catalytic activity and long-term stability in the production of syngas from high-temperature methane reforming. By adjusting the feed composition, a syngas with an adjustable H2 / CO molar ratio within the range of 1.0 to 3.0 can be obtained, flexibly matching the differentiated requirements of downstream processes such as methanol synthesis, Fischer-Tropsch synthesis, and carbonyl synthesis for feed gas composition.

[0018] In addition to the objectives, features, and advantages described above, the present invention has other objectives, features, and advantages. The present invention will now be described in further detail. Attached Figure Description

[0019] The accompanying drawings, which form part of this application, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings:

[0020] Figure 1 These are transmission electron microscope (TEM) images of the catalyst obtained in Example 8 of this invention, wherein: a is a catalyst morphology image, b is a HAADF image, c is an EDS-Mapping image of La, d is an EDS-Mapping image of Ca, e is an EDS-Mapping image of Ce, f is an EDS-Mapping image of Ti, g is an EDS-Mapping image of Ni, and h is an EDS-Mapping image of O.

[0021] Figure 2 The images shown are transmission electron microscope (TEM) images of the catalyst obtained in Comparative Example 1. In the images, a is the catalyst morphology, b is the HAADF image, c is the EDS-Mapping image of La, d is the EDS-Mapping image of Ca, e is the EDS-Mapping image of Ti, f is the EDS-Mapping image of Ni, and g is the EDS-Mapping image of O.

[0022] Figure 3 This is a graph showing the long-term reaction stability evaluation results of the catalyst obtained in Example 8. Detailed Implementation

[0023] The embodiments of the present invention will be described in detail below. The specific embodiments described herein are merely illustrative of the present invention and are not intended to limit the present invention.

[0024] Example 1

[0025] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 2.042 g of tetrabutyl titanate, and 1.163 g of nickel nitrate hexahydrate. Then weigh 0.523 g of barium nitrate and 0.423 g of strontium nitrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.916 g of citric acid and 1.110 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Ba 0.2 Sr 0.2 Ti 0.6 Ni 0.4 O x The content of Ni is 12.1 wt%, the content of Ba is 14.1 wt%, and the content of Sr is 9.0 wt%.

[0026] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 1 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0027] Example 2

[0028] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 2.042 g of tetrabutyl titanate, and 1.163 g of nickel nitrate hexahydrate. Then weigh 0.513 g of magnesium nitrate hexahydrate and 0.472 g of calcium nitrate tetrahydrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.916 g of citric acid and 1.110 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Mg 0.2 Ca 0.2 Ti0.6 Ni 0.4 O x The content of Ni is 14.5 wt%, the content of Mg is 3.0 wt%, and the content of Ca is 4.9 wt%.

[0029] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 2 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0030] Example 3

[0031] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 2.042 g of tetrabutyl titanate, and 1.163 g of nickel nitrate hexahydrate. Then weigh 0.472 g of calcium nitrate tetrahydrate and 0.428 g of zirconium nitrate pentahydrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.532 g of citric acid and 1.055 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Ca 0.2 Zr 0.1 Ti 0.6 Ni 0.4 O x The content of Ni is 14.1 wt%, the content of Ca is 4.8 wt%, and the content of Zr is 5.5 wt%.

[0032] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 3 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0033] Example 4

[0034] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 2.042 g of tetrabutyl titanate, and 1.163 g of nickel nitrate hexahydrate. Then weigh 0.523 g of barium nitrate and 0.428 g of zirconium nitrate pentahydrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.532 g of citric acid and 1.055 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Ba 0.2 Zr 0.1 Ti 0.6 Ni 0.4 O x The content of Ni is 12.6 wt%, the content of Ba is 14.8 wt%, and the content of Zr is 4.9 wt%.

[0035] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 4 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0036] Example 5

[0037] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 2.042 g of tetrabutyl titanate, and 1.163 g of nickel nitrate hexahydrate. Then weigh 0.434 g of cerium nitrate hexahydrate and 0.423 g of strontium nitrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.532 g of citric acid and 1.055 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Sr 0.2 Ce 0.1 Ti 0.6 Ni 0.4 O x The content of Ni is 13.0 wt%, the content of Sr is 9.7 wt%, and the content of Ce is 7.7 wt%.

[0038] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 5 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0039] Example 6

[0040] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 1.361 g of tetrabutyl titanate, and 1.744 g of nickel nitrate hexahydrate. Then weigh 0.472 g of calcium nitrate tetrahydrate and 0.423 g of strontium nitrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.916 g of citric acid and 1.110 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Ca 0.2 Sr 0.2 Ti 0.4 Ni 0.6 O x The content of Ni is 20.3 wt%, the content of Ca is 4.6 wt%, and the content of Sr is 10.1 wt%.

[0041] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 6 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0042] Example 7

[0043] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 2.382 g of tetrabutyl titanate, and 0.872 g of nickel nitrate hexahydrate. Then weigh 0.523 g of barium nitrate and 0.472 g of calcium nitrate tetrahydrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.916 g of citric acid and 1.110 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Ba 0.2 Ca 0.2 Ti 0.7 Ni 0.3 O x The content of Ni is 9.5 wt%, Ba is 14.8 wt%, and Ca is 4.3 wt%.

[0044] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 7 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0045] Example 8

[0046] 1. Catalyst Preparation: S1. Weigh 1.732 g of lanthanum nitrate hexahydrate, 2.042 g of tetrabutyl titanate, and 1.163 g of nickel nitrate hexahydrate. Then weigh 0.472 g of calcium nitrate tetrahydrate and 0.434 g of cerium nitrate hexahydrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.532 g of citric acid and 1.055 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry at 100 °C for 12 hours until a dry gel precursor is formed. Place it on a heating plate at 400 °C and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800 °C for 6 hours at a heating rate of 2 °C / min. S3. Reduce the obtained sample at 850 °C for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.4 Ca 0.2 Ce 0.1 Ti 0.6 Ni 0.4 O x The content of Ni is 13.7 wt%, the content of Ca is 4.7 wt%, and the content of Ce is 8.2 wt%.

[0047] 2. Activity Evaluation: Under normal pressure, methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 8 at a molar ratio of 1~3:1~2:0~6 and space velocities of 20000, 25000, 33400, 41800, and 46000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 1.

[0048] Table 1. Comparison of methane reforming performance of 0.10g catalysts from different embodiments at a reaction temperature of 750℃.

[0049] The above examples demonstrate that a Ni metal content of 10-18 wt% provides sufficient active sites, preventing excessive nickel from causing sintering and carbon buildup, while a content that is too low results in insufficient activity; in particular, the catalytic effect is better when the Ni metal content is 11-15 wt%. A M metal content of 4-30 wt% can produce moderate crystal distortion, increase oxygen vacancies, optimize nickel precipitation, and improve resistance to carbon buildup and sintering. A M metal content that is too low results in poor modification, while a content that is too high easily generates impurities that cover active sites, reducing performance. The preferred M metal content is 5-25 wt%.

[0050] Figure 1 The image shows a transmission electron microscope (TEM) image of the catalyst obtained in Example 8. As can be seen from the image, Ni nanoparticles are clearly dissolved on the surface of the perovskite support, which can increase the contact area between the Ni nanoparticles and the reaction substrate, thus improving the reaction activity.

[0051] Figure 3 The results of a long-term reaction stability evaluation of the catalyst obtained in Example 8 were obtained by introducing methane, carbon dioxide, and water vapor in a molar ratio of 3:1:2 at a space velocity of 25000 mL / g / h into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Example 8 under normal pressure and at 750°C. Figure 3 It can be seen that the catalyst has very stable reaction performance.

[0052] Table 1 shows that the perovskite catalyst prepared in this invention exhibits excellent performance under different reaction conditions and can produce syngas with different H2 / CO molar ratios. In particular, the Ca and Ce modified catalyst obtained in Example 8 achieves a CH4 conversion rate as high as 86.5% at a space velocity of 25000 mL / g / h, and its long-cycle reaction stability reaches 1300 h.

[0053] Comparative Example 1

[0054] 1. Catalyst preparation:

[0055] S1. Weigh 3.464 g of lanthanum nitrate hexahydrate, 2.042 g of tetrabutyl titanate, and 1.163 g of nickel nitrate hexahydrate. Then weigh 0.472 g of calcium nitrate tetrahydrate, add 52 mL of ethanol and stir to dissolve. Then add 7.685 g of citric acid and 1.242 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel.

[0056] S2. After drying at 100℃ for 12 hours until it becomes a dry gel precursor, place it on a heating plate at 400℃ and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800℃ for 6 hours at a heating rate of 2℃ / min.

[0057] S3. The obtained sample was reduced at 850℃ for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.8 Ca 0.2 Ti 0.6 Ni 0.4 O3, of which Ni content is 10.7 wt% and Ca content is 3.6 wt%.

[0058] 2. Activity evaluation:

[0059] Methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Comparative Example 1 at a molar ratio of 1–3:1–2:0–6 and space velocities of 20,000, 25,000, 33,400, 41,800, and 46,000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 2.

[0060] Figure 2 The image shows a transmission electron microscope (TEM) image of the catalyst obtained in Comparative Example 1. As can be seen from the image, no Ni nanoparticles were dissolved on the surface of the perovskite support, indicating that the absence of A-site defects cannot promote the dissolution of Ni nanoparticles.

[0061] Comparative Example 2

[0062] 1. Catalyst preparation:

[0063] S1. Weigh 3.464 g of lanthanum nitrate hexahydrate, 1.361 g of tetrabutyl titanate, and 1.745 g of nickel nitrate hexahydrate. Then weigh 0.434 g of cerium nitrate hexahydrate, add 52 mL of ethanol and stir to dissolve. Then add 7.301 g of citric acid and 1.180 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel.

[0064] S2. After drying at 100℃ for 12 hours until it becomes a dry gel precursor, place it on a heating plate at 400℃ and heat for 1 hour. After cooling to room temperature, grind the obtained sample thoroughly and calcine it in a muffle furnace at 800℃ for 6 hours at a heating rate of 2℃ / min.

[0065] S3. The obtained sample was reduced at 850℃ for 1 hour under a hydrogen atmosphere to obtain catalyst La. 0.8 Ce 0.1 Ti 0.4 Ni 0.6 O x The content of Ni is 15.7 wt% and the content of Ce is 6.2 wt%.

[0066] 2. Activity evaluation:

[0067] Methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Comparative Example 2 at a molar ratio of 1–3:1–2:0–6 and space velocities of 20,000, 25,000, 33,400, 41,800, and 46,000 mL / g / h, respectively, under normal pressure, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 2.

[0068] Comparative Example 3

[0069] 1. Catalyst preparation:

[0070] Ni prepared by impregnation method 0.4 / La 0.4 Ba 0.2 Zr 0.1 Ti 0.6 0x, the specific steps are as follows:

[0071] S1. Weigh 1.732 g of lanthanum nitrate hexahydrate and 2.042 g of tetrabutyl titanate, then weigh 0.523 g of barium nitrate and 0.428 g of zirconium nitrate pentahydrate. Add 52 mL of ethanol and stir to dissolve. Then add 6.532 g of citric acid and 1.055 g of ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. Dry at 100 °C for 12 hours until it becomes a dry gel precursor, then cool to room temperature.

[0072] S2. Weigh 1.163 g of nickel nitrate hexahydrate and dissolve it in 3 mL of deionized water. Add the resulting solution dropwise to the dry gel precursor. Let it stand at room temperature for 6 hours. Then, transfer it to an oven and dry it at 100 °C for 12 hours. After that, transfer it to a muffle furnace and heat it to 800 °C at a heating rate of 2 °C / min. Then, calcine it for 6 hours. After the sample is cooled to room temperature, grind it.

[0073] S3. The obtained sample was reduced at 850°C for 1 hour under a hydrogen atmosphere to obtain the catalyst Ni. 0.4 / La 0.4 Ba 0.2 Zr 0.1 Ti 0.6 O x The content of Ni is 12.6 wt%, the content of Ba is 14.8 wt%, and the content of Zr is 4.9 wt%.

[0074] 2. Activity evaluation:

[0075] Methane, carbon dioxide, and water vapor were introduced into a fixed-bed reactor containing 0.10 g of the catalyst obtained in Comparative Example 3 at atmospheric pressure in a molar ratio of 1–3:1–2:0–6 and space velocities of 20,000, 25,000, 33,400, 41,800, and 46,000 mL / g / h, respectively, and the reaction was carried out at 750 °C. The catalytic performance is shown in Table 2.

[0076] Table 2. Comparison of methane reforming performance of 0.10g of different comparative catalysts at a reaction temperature of 750℃.

[0077] The test data in Table 2, combined with the test data in Table 1, show that the catalysts with only one type of M metal in Comparative Examples 1 and 2 have significantly poor performance, and Comparative Example 3 shows that the catalysts prepared by the impregnation method have poor performance.

[0078] The above description, in conjunction with specific preferred embodiments, provides a further detailed explanation of the present invention. It should not be construed that the specific implementation of the present invention is limited to these descriptions. For those skilled in the art, various simple deductions and substitutions can be made without departing from the inventive concept, and all such modifications and substitutions should be considered within the scope of protection of the present invention.

Claims

1. A method for preparing a catalyst for methane reforming to syngas, characterized in that, Includes the following steps: S1. Weigh out the nickel source, lanthanum source, and titanium source that constitute the perovskite body, then weigh out the M metal salt, add ethanol and stir to dissolve, then add citric acid and ethylene glycol and stir to dissolve at room temperature to obtain a uniform and viscous hydrogel. S2. Dry the hydrogel until it becomes a dry gel precursor, namely, a perovskite oxide La with A-site defects and modified by the introduction of two additives. a1 M a2 Ti b1 Ni b2 O x The precursor, wherein the A-site elements include La and M, the total molar sum of La and M is a1+a2, and 0.5≤a1+a2<1, M is at least two of Ba, Sr, Mg, Ca, Ce, and Zr, and the B-site elements include Ti and Ni, the total molar sum of Ti and Ni is b1+b2, is 1. The precursor is heat-treated at a temperature of 350~450℃ for 0.5~2 hours, cooled to room temperature and then thoroughly ground. The ground sample is then transferred to a muffle furnace for calcination. S3. The calcined sample was reduced to the catalyst La under a certain temperature and hydrogen atmosphere. a1 M a2 Ti b1 Ni b2 O x .

2. The method for preparing the methane reforming catalyst for syngas production according to claim 1, characterized in that, The catalyst La a1 M a2 Ti b1 Ni b2 O x Based on the total weight of the catalyst, the Ni metal content is 9~21wt%; the M metal content is 4~30wt%.

3. The method for preparing the catalyst for methane reforming to syngas according to claim 2, characterized in that, The catalyst La a1 M a2 Ti b1 Ni b2 O x The total weight of the catalyst is 11-15 wt% Ni and 5-25 wt% M.

4. The method for preparing the methane reforming catalyst for syngas production according to claim 1, characterized in that, The total molar sum of the elements at position A, a1+a2, is 0.6~0.9; the total molar sum of the elements at position B, b1+b2, is 1, where b2 is 0.2~0.

7.

5. The method for preparing the methane reforming catalyst for syngas production according to claim 4, characterized in that, The total molar sum of the B-position elements, b1+b2, is 1, where b2 is 0.3~0.

6.

6. The method for preparing the catalyst for methane reforming to syngas according to claim 1, characterized in that, The nickel source is one of nickel nitrate hexahydrate, nickel acetylacetonate, and nickel chloride; the lanthanum source is one of lanthanum nitrate hexahydrate, lanthanum acetylacetonate, and lanthanum chloride; the titanium source is one of tetrabutyl titanate, titanium nitrate, and titanium acetylacetonate; and the M metal salt is one of barium nitrate, strontium nitrate, magnesium nitrate hexahydrate, calcium nitrate tetrahydrate, cerium nitrate hexahydrate, zirconium nitrate pentahydrate, barium acetylacetonate, strontium acetylacetonate, magnesium acetylacetonate, calcium acetylacetonate, cerium acetylacetonate, zirconium acetylacetonate, barium chloride, strontium chloride, magnesium chloride, calcium chloride, cerium chloride, and zirconium chloride.

7. The method for preparing the methane reforming catalyst for syngas production according to claim 1, characterized in that, In step S1, the molar ratio of citric acid to all metal ions is 1~4:1; the molar ratio of ethylene glycol to all metal ions is 0.5~2:1; all metal ions include A-site element metal ions and B-site element metal ions; in step S2, the calcination temperature is 700~900℃ and the calcination time is 0.5~10 hours; in step S3, the reduction temperature is 700~900℃ and the reduction time is 0.5~10 hours.

8. The method for preparing the methane reforming catalyst for syngas production according to claim 7, characterized in that, In step S1, the molar ratio of citric acid to all metal ions is 1~2.5:1; the molar ratio of ethylene glycol to all metal ions is 0.6~1.5:1; in step S2, the calcination temperature is 750~850℃ and the calcination time is 2~8 hours; in step S3, the reduction temperature is 750~850℃ and the reduction time is 1~4 hours.

9. A catalyst for the reforming of methane to syngas, characterized in that, The catalyst for methane reforming to syngas is prepared using the method described in any one of claims 1 to 8.

10. A method for producing syngas from methane through reforming, characterized in that, The catalyst for methane reforming to syngas as described in claim 9 is used, and the catalyst for methane reforming to syngas is placed in a fixed-bed reactor. The reaction conditions for methane reforming to syngas include: The reaction of methane reforming to produce syngas is carried out in a fixed-bed reactor at a reaction temperature of 600-900℃ and a reaction pressure of 0-4MPa; the reaction space velocity is 5000-60000mL / g / h, and the molar ratio of methane, carbon dioxide and water vapor is 0.5-5:0.5-5:0-10.